2015
DOI: 10.1021/am504742q
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Interfacial Interaction and CO2 Separation Performance of Mixed Matrix Membrane by Incorporating Polyethylenimine-Decorated Metal–Organic Frameworks

Abstract: Polyethylenimine (PEI) was immobilized by MIL-101(Cr) (∼550 nm) via a facile vacuum-assisted method, and the obtained PEI@MIL-101(Cr) was then incorporated into sulfonated poly(ether ether ketone) (SPEEK) to fabricate mixed matrix membranes (MMMs). High loading and uniform dispersion of PEI in MIL-101(Cr) were achieved as demonstrated by ICP, FT-IR, XPS, and EDS-mapping. The PEI both in the pore channels and on the surface of MIL-101(Cr) improved the filler-polymer interface compatibility due to the electrosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
93
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(97 citation statements)
references
References 55 publications
(100 reference statements)
1
93
0
Order By: Relevance
“…[135][136][137][138][139][140] The Ag@MIL-101 porous material, with different Ag loadings, was prepared by Liu et al 134 via a simple impregnation-reduction methodology immobilizing Ag nanoparticles into the cages of MIL-101(Cr). This material exhibits outstanding bifunctionality: i) on the one hand, Ag@MIL-101 is capable to retain CO 2 in its porous structure; and ii) on the other hand, the CO 2 is converted into compounds with carboxylic acid groups through C-H bond activation of the terminal alkynes.…”
Section: -Co 2 Capturementioning
confidence: 99%
“…[135][136][137][138][139][140] The Ag@MIL-101 porous material, with different Ag loadings, was prepared by Liu et al 134 via a simple impregnation-reduction methodology immobilizing Ag nanoparticles into the cages of MIL-101(Cr). This material exhibits outstanding bifunctionality: i) on the one hand, Ag@MIL-101 is capable to retain CO 2 in its porous structure; and ii) on the other hand, the CO 2 is converted into compounds with carboxylic acid groups through C-H bond activation of the terminal alkynes.…”
Section: -Co 2 Capturementioning
confidence: 99%
“…21,22 High additive loading generally causes severe embrittlement, though a few recent studies have reported stable MMM films through targeted polymer-additive interactions. 12,[23][24][25][26] Similarly, adsorption of polymer chains in super-porous additives have been used to stop age-related permselectivity loss in glassy MMM. 12,[27][28][29] To date, there is no complete model describing the complex polymer-additive interactions responsible for MMM properties and little is known about how additive incorporation affects the mechanical resilience of polymer nanocomposites with aging.…”
Section: Introductionmentioning
confidence: 99%
“…15,20,21,26,32,37,69,[135][136][137][138] Essentially, these properties are determined by the interactions among gas molecules, polymers and fillers, which can be computed using molecular simulation with verified force fields accurately. Molecular modeling can reach tens of nanoseconds and nanometers at maximum, which is large enough to compute the gas transportation in the homogenous phases like pure polymer membranes and inorganic porous fillers.…”
Section: Predictive Models For Gas Separation Performancementioning
confidence: 99%